Structure-Guided Design of N-Methylpropargylamino- Quinazoline Derivatives as Multipotent Agents for the Treatment of Alzheimer's Disease - Svobodova, Barbora; Pulkrabkova, Lenka; Panek, Dawid; Misiachna, Anna; Kolcheva, Marharyta; Andrys, Rudolf; Handl, Jiří; Čapek, Jan; Nývltová, Pavlína; Roušar, Tomáš; Prchal, Lukas; Hepnarova, Vendula; et al. (MDPI AG (Multidisciplinary Digital Publishing Institute), 2023)
Alzheimer's disease (AD) is a complex disease with an unknown etiology. Available treatments, limited to cholinesterase inhibitors and N-methyl-d-aspartate receptor (NMDAR) antagonists, provide symptomatic relief only. As single-target therapies have not proven effective, rational specific-targeted combination into a single molecule represents a more promising approach for treating AD, and is expected to yield greater benefits in alleviating symptoms and slowing disease progression. In the present study, we designed, synthesized, and biologically evaluated 24 novel N-methylpropargylamino-quinazoline derivatives. Initially, compounds were thoroughly inspected by in silico techniques determining their oral and CNS availabilities. We tested, in vitro, the compounds' effects on cholinesterases and monoamine oxidase A/B (MAO-A/B), as well as their impacts on NMDAR antagonism, dehydrogenase activity, and glutathione levels. In addition, we inspected selected compounds for their cytotoxicity on undifferentiated and differentiated neuroblastoma SH-SY5Y cells. We collectively highlighted II-6h as the best candidate endowed with a selective MAO-B inhibition profile, NMDAR antagonism, an acceptable cytotoxicity profile, and the potential to permeate through BBB. The structure-guided drug design strategy applied in this study imposed a novel concept for rational drug discovery and enhances our understanding on the development of novel therapeutic agents for treating AD.
Strukturní design N-methylpropargylamino-chinazolinových derivátů jako multipotentních činidel pro léčbu Alzheimerovy choroby
Keywords: Alzheimer's disease; Acetylcholinesterase; Enzyme inhibition; N-methyl-d-aspartate receptor; Monoamine oxidase A/B; Multi-target directed ligands; Alzheimerova choroba; Acetylcholinesteráza; Inhibice enzymů; N-methyl-d-aspartátový receptor; Monoaminooxidáza A/B; "Vícecílové" ligandy